Household costs and care seeking patterns associated with COVID-19 in Blantyre, Malawi. - Jobiba Chinkhumba; Samuel Mpinganjira; Andrew Kumitawa; Mercy Malopa; Dalitso Longwe; Vincent Samuel Phiri; Tonney S Nyirenda; Victor Mwapasa (PLOS Global Public Health)
Economic consequences of COVID-19 illness and healthcare use for households in low income countries are not well known. We estimated costs associated with COVID-19 care-seeking and treatment from a household perspective and assessed determinants of treatment costs. A cross-sectional household survey was conducted between December 2020 and November 2021 in urban and peri-urban areas of Blantyre district. Adults (age ≥18 years) with confirmed COVID-19 were asked to report the symptoms they experienced or prompted them to seek COVID-19 tests as well as healthcare seeking behaviors preceding and following COVID-19 diagnosis. For individuals who sought healthcare, information on out-of-pocket expenditures incurred while seeking and receiving care including on transport, food etc. by both the patients and their guardians was collected. Finally, data on time use seeking, receiving care and during convalesces was recorded. Multivariate Generalized Linear Models were used to evaluate association between household COVID-19 costs and their determinants. Of 171 individuals who took part in the study, the average age was 40.7 years, standard deviation (SD) 15.0, and 50.8% were females. Most participants (85.3%) were symptomatic. Of these, 67.8% sought care at health facilities and the majority (91.7%) were treated as outpatients. The average total household cost associated with COVID-19 seeking, receiving care and convalescence was $62.81 (SD $126.02). Average costs for outpatient and inpatient cases were $52.96 (SD $54.35) and $172.39 (SD $407.08), respectively. Average out-of-pocket household expenditures were $42.62 (SD $123.10), accounting for 62% of total household costs. Being a male COVID-19 patient and engagement in formal employment were significantly associated with high COVID-19 household costs. Households face high economic burden related to COVID-19 sickness and healthcare use. Social policies that support households cope with both the direct and indirect COVID-19 cost are needed to ensure access to healthcare and protect households from COVID-19 related shocks.